Instytucja „przestępstwa wojskowego” – uwagi de lege ferenda - Ziółkowska, Agata (PRAWO i WIĘŹ, 2025)
This paper attempts to justify the concept of the need to introduce a normative definition of the concept of „military crime” into the current Penal Code of 1997. It should be noted that since January 1, 1970 (i.e. since the entry into force of the previously applicable code regulation - i.e. the Penal Code of 1969) continuously until today, the concept of „military crime” has been used in the broadly understood Polish criminal law system (nor its legal definition) does not formally exist. In other words, it was not decreed in the text of the Penal Code of 1969 nor under the legal solutions adopted in the Penal Code of 1997. This is an incomprehensible practice, especially when one takes into account the arguments of a historical, systemic, functional-doctrinal and international nature presented in this paper, which directly support the validity of the reported de lege ferenda task of introducing a normative definition into the code regulations the concept of „military crime”. The implementation of this task will undoubtedly contribute to filling the current legal gap and will also contribute to the (symbolic, but still) systematisation of the institutions of military criminal law and their harmonisation with the provisions of international legal instruments.